PENGARUH VOLUME AIR DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays saccharata Sturt) - Warman, Indra; Khoiri, M. Amrul; ', Husnayetti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of the research was to determine influence of water volume and chicken manure on the growth and crop production of sweet corn and see the best treatment. Research was carried out in gauze house, experimental garden Faculty Agriculture University of Riau. The research carried out by using a completely randomized design (CRD) consisting of two factors and three replications is the first faktor is the volume of water: water volume 1400 ml, 1050 ml of water, volume and water volumeÂ  of 700 ml. the secand faktor of chicken manure that is: with second commission of chicken manure 75 g/polybag, chicken manure 150 g/polybag, chicken manure and 225 g/polybag. Parameter is the height of the plants, the emergence of the male flowers, the riset of female flowers, hervisting, weight percob, cob length, cob diameter, cob weight without cornhusk. Treatment volume of 1400 ml ofÂ  water and 225 g of chicken manure/polybag give the best effecton weight cob without cornhusk is 439,8 9/polybag. Keywords : Giving water volume, chicken manure fertilizer, sweet corn